Blockchain Technology for Financial Sector – An Overview - Agarwal, Madhu Agnihotri Nee (International Journal of Computer Sciences and Engineering, 2025)
The Blockchain concept permits the simultaneous working of multiple stakeholders of business by eliminating the intermediary. It makes the transaction possible even if the stakeholders do not trust each other. Many companies including the security exchanges have developed blockchain based applications in last two years to make payments internally within the company as well as externally to trade with outside world. However, there are many who are still hesitating in adopting the system. Security and monitoring mechanism to administer blockchain are major issues of concern among the regulators and adopters of the technology. This paper is an attempt to explore the various dimensions of blockchain technology in context of financial sector. The technology is continuously developing and hence a critical understanding is required to reap its all the benefits.